Assessing barriers and facilitators to transition in sickle cell disease care prior to implementation of a formalized program. Issue 4 (8th January 2023) - Sheppard, Sydney; Hellemann, Gerhard; Lebensburger, Jeffrey; Kanter, Julie
Abstract: Over 95% of children with sickle cell disease (SCD) survive into adulthood in the United States. However, early mortality remains a problem, especially in persons between the ages of 18 and 35. One possible explanation for the increased mortality rate in young adults is difficulties in engaging in care during the transition from a heavily contiguous pediatric healthcare model to a more self‐reliant adult healthcare model. The goal of this study was to identify potential facilitators and barriers to a successful transfer in care from the pediatric to adult SCD program before the formation of a formal transition program. This is a retrospective cohort study of transition outcomes for 472 individuals with SCD (all genotypes) treated at the University of Alabama at Birmingham (UAB) sickle cell clinic (aged 18–24). The primary outcome was whether the patient continued care in (any) adult SCD program (defined as being seen at least once in an adult hematology/SCD clinic). One hundred eighty‐eight (45%) transition age patients successfully transferred to adult care. Facilitators to successful transfer in care included being treated at the same hospital for both pediatric and adult programs, having the genotype HbSS, and/or receiving an SCD‐modifying therapy at the time of transition (hydroxyurea and/or red cell transfusion therapy). Of primary interest, many of the patients who failed to transition to an adult clinic were lost to follow‐up prior to 15 years of age. Importantly, these patients who had previously been labeled as "transition failures, " were lost to follow‐up long before the transition age. Early engagement is needed for this population.